Turbulent convective heat transfer in helical tube with twisted tape insert - Liaw, K.L. (Elsevier Ltd, 2021)
Enhancement of heat transfer has been a main focus in thermal-fluid engineering field among the other aspects in industrial for decades. Despite numerous studies have been done on turbulent flows, helical tubes, and twisted tapes related to enhancement, no study has been done on the combination of all three components in augmentation of heat transfer. The objective of this study is to numerically investigate heat transfer of turbulent flow in helical tube with twisted tape insert subjected to constant wall temperature. A three-dimensional computational fluid dynamic model was developed and validated against experimental measured data and correlations. The model was then used to evaluate the turbulent convective heat transfer in straight and helical tube with and without twisted tape insert. To obtain comprehensive view on the heat transfer performance, the effect of twist ratio and inlet Reynolds number are evaluated as well. The insertion of twisted tape is found to increase the intensity of secondary flow in the radial direction. Helical tube with twisted tape insert was found to have higher heat transfer performance. The results show that for every case, the higher the inlet Reynolds number, the heat transfer increases proportionally while friction coefficient drops with decreasing amount of decrement. It is found that helical coiled tube with twisted tape at twist ratio of 7.86 has the highest performance among the configuration studied after taking consideration of heat transfer, friction coefficient and entropy generation. Finally, correlations of Nu and f are developed to predict the heat transfer and pressure drop within considered range of parameters in this study. This study serves as a foundation on the development of a high-performance heat exchanger for industrial application. Â© 2021